Permanent and temporary pacemaker implantation after orthotopic heart transplantation - Bacal,Fernando (2000)
PURPOSE:To determine the indication for and incidence and evolution of temporary and permanent pacemaker implantation in cardiac transplant recipients. METHODS: A retrospective review of 114 patients who underwent orthotopic heart transplantation InCor (Heart Institute USP BR) between March 1985 and May 1993. We studied the incidence of and indication for temporary pacing, the relationship between pacing and rejection, the need for pemanent pacing and the clinical follow-up. RESULTS: Fourteen of 114 (12%)heart transplant recipients required temporary pacing and 4 of 114 (3.5%) patients required permanent pacing. The indication for temporary pacing was sinus node dysfunction in 11 patients (78.5%) and atrioventricular (AV) block in 3 patients (21.4%). The indication for permanent pacemaker implantation was sinus node dysfunction in 3 patients (75%) and atrioventricular (AV) block in 1 patient (25%). We observed rejection in 3 patients (21.4%) who required temporary pacing and in 2 patients (50%) who required permanent pacing. The previous use of amiodarone was observed in 10 patients (71.4%) with temporary pacing. Seven of the 14 patients (50%) died during follow-up. CONCLUSION: Sinus node dysfunction was the principal indication for temporary and permanent pacemaker implantation in cardiac transplant recipients. The need for pacing was related to worse prognosis after cardiac transplantation.